Citra Merek, Harga, dan Kualitas Produk sebagai Prediktor Keputusan Pembelian Foundation Maybelline di Shopee - Laela Rahmawati; Arie Hendra Saputro; Dadan Abdul Aziz Mubarok; Ridho Riadi Akbar (Jurnal Bisnis, Manajemen, dan Ekonomi, 2026)
The rapid growth of cosmetic products in digital marketplaces has intensified competition among global, local, and emerging brands. This study examines the effects of brand image, price, and product quality on purchasing decisions for Maybelline foundation products on Shopee. A quantitative explanatory survey was conducted involving 100 consumers who had purchased and used Maybelline foundation through Shopee. Data were collected using a structured questionnaire and analyzed using descriptive statistics, classical assumption tests, and multiple linear regression. The results show that brand image, price, and product quality each have a positive and significant effect on purchasing decisions. Product quality has the strongest relative contribution, followed by price and brand image. Simultaneously, the three predictors significantly explain purchasing decisions, with an R-square value of 0.674, indicating that 67.4% of the variation in purchasing decisions is explained by the model. These findings imply that Maybelline should prioritize consistent product performance, strengthen consumers’ perception of price fairness, and maintain a relevant brand image in the marketplace. Future studies may include online customer reviews, electronic word of mouth, promotion, and trust to provide a broader explanation of digital purchasing behavior